(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This paper examines the physicochemical and electrical properties of silicon containing binary complexes of manganese (Mn) and selenium (Se) impurity atoms. The relevance of this topic stems from the need to create new functional materials for micro- and optoelectronics, where controlled doping offers the potential for modifying conductivity, photosensitivity, and spin-dependent effects. It was established that the simultaneous introduction of manganese and selenium into the silicon lattice leads to the formation of stable defect complexes with unique energy characteristics. Experimental studies using DLTS spectroscopy, infrared photoconductivity, and electron microscopy analysis demonstrated that such complexes are capable of altering the charge carrier lifetime, forming new levels in the band gap, and extending the spectral sensitivity of the material to the near-infrared range. Theoretical modeling using the density functional theory method confirmed the formation of new stable states and predicted the possibility of their practical use in spintronic and photonic devices.